RELAPSING POLYCHONDRITIS: FROM ETIOPATHOGENESIS TO THERAPY - Živković, Valentina (Acta medicae Medianae, 2024)
Relapsing polychondritis (RP) is a rare autoimmune systemic disease of nature, with insufficiently elucidated etiopathogenesis, characterized by a predominantly relapsing-remitting course, involving elastic, hyaline and fibrous cartilage and tissues abundant in proteoglycans. It may lead to anatomical and functional impairments, with a potentially fatal outcome despite treatment. It usually manifests in the form of auricular and nasal chondritis and polyarthritis. Involvement of the laryngotracheobronchial tree, as well as heart valves and aorta, with the onset of secondary infections of primarily lower portions of the respiratory tract, are the most common reasons for the lethal outcome. Involvement of the eye in the form of episcleritis, scleritis etc., involvement of the inner ear in the form of vestibular disorders and sensorineuronal symptoms, as well as central and peripheral nervous system involvement, comprise a probable clinical spectrum of RP. The diagnosis of the disease is usually significantly delayed; for the diagnosis, clinical presentation is essential, while laboratory findings play only a supportive role, and imaging methods (CT, PET-CT, MRI) are important in disease activity assessments. Mild forms of RP should be treated with non-steroidal anti-inflammatory agents and low doses of corticosteroids, while severe forms are treated using higher or, as needed, pulse doses of corticosteroids, and with conventional and biological disease-modifying drugs (DMARDs). More advanced forms of aortic and valvular disease require surgical treatment.
Keywords: cartilage, relapsing polychondritis, therapy